2008
DOI: 10.2166/wst.2008.628
|View full text |Cite
|
Sign up to set email alerts
|

Ecological engineering of bioaugmentation from side-stream nitrification

Abstract: Wastewater treatment relies on careful integration of environmental engineering with microbial ecology. This would seem to be particularly the case when attempting to enhance survivability of organisms introduced from outside the main-stream reactor, i.e. bioaugmentation. Molecular biology tools were utilised in this study to assist in understanding the mechanisms of successful bioaugmentation. Molecular fingerprinting showed that side-stream reactor configuration strongly influenced ammonia-oxidising bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Growing nitrifying species separately from the recycled sludge isolates the nitrifiers from toxic or nitrifier-inhibitory compounds in the process influent (Ng et al, 1987). Smith et al (2008) showed that biodiversity of nitrifying species was better preserved in the isolated enricher reactors than in the reaeration reactors when both received the high ammonia sludge supernatant as enrichment substrate. Using molecular biology, Smith et al (2008) showed that the ER-RAS approach produces a monoculture of the nitrifying species in the augmented reactor, whereas multicultures were always found in reactors augmented by offline SBRs (enricher reactors).…”
Section: Comparison Of Three Bioaugmentation Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing nitrifying species separately from the recycled sludge isolates the nitrifiers from toxic or nitrifier-inhibitory compounds in the process influent (Ng et al, 1987). Smith et al (2008) showed that biodiversity of nitrifying species was better preserved in the isolated enricher reactors than in the reaeration reactors when both received the high ammonia sludge supernatant as enrichment substrate. Using molecular biology, Smith et al (2008) showed that the ER-RAS approach produces a monoculture of the nitrifying species in the augmented reactor, whereas multicultures were always found in reactors augmented by offline SBRs (enricher reactors).…”
Section: Comparison Of Three Bioaugmentation Approachesmentioning
confidence: 99%
“…Smith et al (2008) showed that biodiversity of nitrifying species was better preserved in the isolated enricher reactors than in the reaeration reactors when both received the high ammonia sludge supernatant as enrichment substrate. Using molecular biology, Smith et al (2008) showed that the ER-RAS approach produces a monoculture of the nitrifying species in the augmented reactor, whereas multicultures were always found in reactors augmented by offline SBRs (enricher reactors). It may be easier to manage the alkalinity loss in the ER-RAS approach because the entire recycle stream is available to buffer the pH decline.…”
Section: Comparison Of Three Bioaugmentation Approachesmentioning
confidence: 99%
“…So far, many studies have measured structural diversity of AOB and stability of ammonia oxidization in main stream activated sludge systems bioaugmented from side-stream reject water treatment systems [5, 15]. Smith and Oerther [16] have also theorized that increased population diversity from input of microorganisms possessing desirable properties from side-stream processes to a mainstream process creates a more robust system that is less susceptible to inhibition or upsets.…”
Section: Introductionmentioning
confidence: 99%
“…So, when it comes to meeting effluent criteria, plant operators may face capacity limits. Instead of increasing sludge retention time and activated sludge tank volumes, alternative strategies like bioaugmentation can be considered (Salem et al 2003;Krhutková et al 2006;Smith et al 2008). The advantage of the bioaugmentation method, which is best applicable to slowly growing communities as AOB, is that it recycles active nitrifier biomass and is thus suited to increase the overall nitrogen removal rate (Rittmann 1996;Smith et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Instead of increasing sludge retention time and activated sludge tank volumes, alternative strategies like bioaugmentation can be considered (Salem et al 2003;Krhutková et al 2006;Smith et al 2008). The advantage of the bioaugmentation method, which is best applicable to slowly growing communities as AOB, is that it recycles active nitrifier biomass and is thus suited to increase the overall nitrogen removal rate (Rittmann 1996;Smith et al 2008). The AOB examined in this study are classified into the b-Proteobacteria, including two genera (Nitrosomonas and Nitrosospira) and the g-Proteobacteria with only one genus (Nitrosococcus) (Wagner et al 1995).…”
Section: Introductionmentioning
confidence: 99%